UML for systems engineering watching the wheels - Holt, Jon (Institution of Engineering and Technology, 2004)
This book has 11 chapters. Chapter 1 deals with system engineering, its problems, quality and complexity. Chapter 2 is based on modelling, particularly UML. Structural modelling and behavioural modelling are discussed in Chapter 3 and Chapter 4 respectively. UML diagrams are discussed in Chapter 5. In Chapter 6, modelling standards, processes and procedures are discussed. Requirements for modelling are discussed in Chapter 7. Life cycle management is discussed in Chapter 8. Chapter 9 covers the system architecture. Extentions of UML are discussed in Chapter 10 and tools for modelling are discussed in Chapter 11.